2012
DOI: 10.1111/j.1551-2916.2012.05437.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Sintering of Nanocrystalline Ni1−xZnxFe2O4 Ferrite Powder and Their Magnetic Properties

Abstract: Nanocrystalline Ni1−xZnxFe2O4 (0 ≤ x ≤ 1.0) powder with grain size of 30 nm was prepared using the spraying‐coprecipitation method. The obtained nanocrystalline Ni1−xZnxFe2O4 powder was sintered using conventional and microwave sintering techniques. The results show that the microstructure and magnetic properties of the sintered samples are obviously improved by microwave sintering of nanocrystalline Ni1−xZnxFe2O4 ferrite powder. The initial permeability of Ni1−xZnxFe2O4 ferrite increases with the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In Ni-Zn ferrites, the magnetic properties measurement show lower coercivity and higher magnetization for the microwave-sintered samples [68]. Th is may be due to contribution of microwaves to the uncoupling eff ect.…”
Section: Conventionalmentioning
confidence: 99%
See 3 more Smart Citations
“…In Ni-Zn ferrites, the magnetic properties measurement show lower coercivity and higher magnetization for the microwave-sintered samples [68]. Th is may be due to contribution of microwaves to the uncoupling eff ect.…”
Section: Conventionalmentioning
confidence: 99%
“…Th e lattice parameter was found to increase much slower with increasing zinc for the microwaveirradiated specimens. Mossbauer spectroscopy studies were performed at room temperature and the resonance lines are much sharper for the irradiated samples and indicating that a microwave-induced recrystallization of the ferrites [68][69]. Nanocrystalline Ni 1−x Zn x Fe 2 O 4 (0 ≤ x ≤ 1.0) powder with average grain size of 30 nm was prepared using the spraying-coprecipitation method.…”
Section: Conventionalmentioning
confidence: 99%
See 2 more Smart Citations
“…Gheisari et al 6 studied the nanocrystalline Ni 0.64 Zn 0.36 Fe 2 O 4 powders by high energy ball milling of ZnO, NiO and Fe 2 O 3 powders. Liu et al 7 prepared nanocrystalline Ni 1-x Zn x Fe 2 O 4 (0≤x≤1.0) powder with grain size of 30 nm using the spraying-coprecipitation method, and the microstructure and magnetic properties of samples after the conventional and microwave sintering were studied. Gabal et al 8 found that egg-white precursor method provided a simple and cost-effective route to synthesize single phase Ni 1-x Zn x Fe 2 O 4 (x=0.0-1.0) nanopowders.…”
Section: Introductionmentioning
confidence: 99%